Bahasa Dan Identitas Dalam Novel Segala Yang Diisap Langit Karya Pinto Anugrah: Pendekatan Antropolinguistik - Putri, Yolanda Z; Usman, Fajri; Marnita, Rina (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study explores the relationship between language and identity in the novel Segala yang Diisap Langit by Pinto Anugrah using an anthropolinguistic approach. Through qualitative analysis, the research focuses on how language is used to reflect and shape the identity of the Minangkabau community. The findings reveal that the use of the Minangkabau language in the novel serves not only as a communication tool but also as a rich cultural identity symbol. The combination of Minangkabau and Indonesian lexicons reflects the characters' struggles with their identities amidst social change. Additionally, the representation of traditions and customs through language acts as a means to preserve inherited cultural values. In this context, language plays a crucial role in maintaining Minangkabau identity and responding to modernization and globalization. This study contributes to understanding the role of language as a medium for negotiating identity within a society undergoing cultural transformation.